(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a novel coronavirus responsible for CODIV 19 pandemic, an international public health emergency. Conventional routes of transmission of SARS-CoV-2 are respiratory droplets and direct surface based contact, similar to SARS-CoV, Middle East respiratory syndrome-related coronavirus (MERS-CoV), and highly pathogenic influenza. Some clinical features of infectivity and viral susceptibility of SARS-CoV-2 are similar to SARS-CoV-1, MERS-CoV, suggesting a difference in the viral tropism despite the phylogenetic homogeneity. The incubation period of SARS-CoV-2 is in line with other coronaviruses, but with lower case fatality rate, although the presence of comorbidities can make it highly lethal. The major concern with SARS-CoV-2 is its ability to spread silently by the asymptomatic and presymptomatic carriers. About 70-80% positive cases of COVID 19 is coming out to be asymptomatic, presymptomatic, or very mild symptomatic which dangerously higher compared to SARS-CoV-1, MERS-CoV, H1N1, and seasonal influenza. Asymptomatic and presymptomatic carriers based silent spreading of SARS-CoV-2 has become a major concern due to short serial interval, and soaring level of virus shedding from the upper respiratory tract. Asymptomatic transmission is making containment measures difficult to implement, now early detection and isolation of asymptomatic and presymptomatic persons can be an effective strategy to control spread. High transmutability and silent infection rate SARS-CoV-2 will hopefully help in the fast development of community herd immunity, assuming to have 12 to 14 months active spread period compared to 18-24 for previous pandemic flu. Mass screening by rapid antibody tests, especially in congregate living conditions, mandatory use face masks, social-distancing, and strict execution of sanitization practices even after the relaxation of lockdown, can effectively help to control the COVID 19 infection rate.